2008
DOI: 10.1080/14631370802018882
|View full text |Cite
|
Sign up to set email alerts
|

Debt sustainability in the EU New Member States: empirical evidence from a panel of eight Central and East European countries

Abstract: This article aims to assess the sustainability of fiscal policies in a panel of eight EU New Member States, namely Bulgaria, the Czech Republic, Estonia, Latvia, Lithuania, Poland, the Slovak Republic and Slovenia. First, using panel data unit-root tests, econometric findings show that the variables public expenditure and revenue are not stationary. However, employing panel cointegration tests, it is found that government spending and revenue are cointegrated. This implies that fiscal policies in these countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…159-172), Stoian andCâmpeanu (2010), andStanek (2014). Llorca and Redzepagic (2008) examine panel of eight new EU Member States (including the Czech Republic, but excluding Hungary). They use data on public expenditure and revenues and on the basis of panel unit root tests and panel co-integration tests find that fiscal policy in these countries is sustainable in the long run.…”
Section: Policy Not Sustainablementioning
confidence: 99%
“…159-172), Stoian andCâmpeanu (2010), andStanek (2014). Llorca and Redzepagic (2008) examine panel of eight new EU Member States (including the Czech Republic, but excluding Hungary). They use data on public expenditure and revenues and on the basis of panel unit root tests and panel co-integration tests find that fiscal policy in these countries is sustainable in the long run.…”
Section: Policy Not Sustainablementioning
confidence: 99%
“…Further, we discriminate between structural and cyclical components of revenues and expenditures in order to place emphasis on the structural component. This is the novelty of this paper when contrasted with previous panel cointegration sustainability studies between revenues and expenditures, such as Westerlund and Prohl (2010), Afonso (2005), Quintos (1995), Schneider (2006), Claeys (2007) and Llorca and Redzepagic (2008). With motivations from Galí et al (2003) who posited that the component of fiscal variables whose variations do not emanate from the influence of cycles represents discretionary fiscal policy, we use fiscal variables adjusted for cyclicallity.. As opined by Blanchard (2006), structural fiscal variables provide a benchmark by which fiscal policy can be judged.…”
Section: Introductionmentioning
confidence: 96%
“…Their results indicated that the fiscal stance of selected CEEC countries is jointly sustainable. Similarly, Llorca and Redzepagic (2008) assessed the sustainability of fiscal policy for eight CEEC countries using panel cointegration analysis and found out these countries pursued sustainable fiscal policies for period 1999-2006 using quarterly data. Boekemeier and Stoian (2018) also investigated debt sustainability in 10 CEEC countries using estimates of a fiscal reaction function in its cubic form over the period 1998-2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainable development in the context of various transformation and transition processes in general could be defined as an especially perspective area and as the main direction of the research on sustainable development (Zavadskas 2008;Dzemydiene 2008;Grundey 2008cGrundey , 2009McNally 1999;Melnikas 1990Melnikas , 2002Munasinghe et al 2001;Perraton 2001;Redding and Venables 2004). The problems and processes of the sustainable development in the transition countries in general , as well as in the Eastern and Central European countries could be defined as an important research area too (Brauers et al 2007;Cohendet and Stojak 2005;Dicken 1998;Goeransson and Soederberg 2005;Hayo and Seifert 2003;Krupka 2007;Lasas 2004;Llorca and Redzepagic 2008;Melnikas 1997Melnikas , 1999Melnikas , 2002Melnikas , 2008aMelnikas and Reichelt 2004;Mzavanadze 2009).…”
Section: Sustainable Development and Creation Of The Knowledge Based mentioning
confidence: 99%